Impacts of Embryonic Thermal Programming on the Expression of Genes Involved in Foie gras Production in Mule Ducks - Massimino, William; Andrieux, Charlotte; Biasutti, Sandra; Davail, Stéphane; Bernadet, Marie-Dominique; Pioche, Tracy; Ricaud, Karine; Gontier, Karine; Morisson, Mireille; Collin, Anne; Panserat, Stéphane; Houssier, Marianne (Frontiers in Physiology, 2021)
Embryonic thermal programming has been shown to improve fatty liver production in overfed mule ducks. However, the mechanisms at the origin of this programming have not yet been characterized. In this study, we investigated the effect of embryonic thermal manipulation (+1°C, 16h/24h from embryonic (E) day 13 to E27) on the hepatic expression of genes involved in lipid and carbohydrate metabolisms, stress, cell proliferation and thyroid hormone pathways at the end of thermal manipulation and before and after overfeeding (OF) in mule ducks. Gene expression analyses were performed by classic or high throughput real-time qPCR. First, we confirmed well-known results with strong impact of OF on the expression of genes involved in lipid and carbohydrates metabolisms. Then we observed an impact of OF on the hepatic expression of genes involved in the thyroid pathway, stress and cell proliferation. Only a small number of genes showed modulation of expression related to thermal programming at the time of OF, and only one was also impacted at the end of the thermal manipulation. For the first time, we explored the molecular mechanisms of embryonic thermal programming from the end of heat treatment to the programmed adult phenotype with optimized liver metabolism.